RETRACTED: The Influence Of Brand Image, Product Quality And Promotion On Product Purchasing Decisions Epson Projectors In Jakarta - Ary Susana Dewi; elwisam elwisam; Kumba Digdowiseiso (Journal of Social Science)
This study aims to analyze the influence of brand image, product quality and promotion on the purchase decision of Epson projectors. The method used in this study is quantitative descriptive with the population in this study being consumers who have purchased Epson projector products. The sampling techniques in this study are nonprobability sampling and purposive sampling The sample used in this study was 100 respondents with consumer criteria who had purchased an Epson projector. The data in this study used primary data by distributing questionnaires processed using Software Statistical Product and Service Solutions. (SPSS 23.0). The data analysis technique used is multiple liner regression analysis. The results of this study show that the variables of brand image, product quality and promotion have a positive and significant effect on purchasing decisions. The variables that have a major contribution in the purchase decision of Epson projector products are first product quality, the second brand image and the third promotion.